The enhancement of employee performance through leadership and individual level variables in three Metropolitan municipalities in South Africa - Smit, Petronella Frederika (University of the Free State, 2022)
South African municipalities are known for poor service delivery, resulting from leaders failing to manage processes and performance. A lack of leadership competencies was cited as one of the reasons for poor employee performance in municipalities. Literature also showed that several individual factors (i.e. employee psychological empowerment, employee workplace spirituality, employee motivation, and employee citizenship behaviour) might play a role in employee performance. However, it is not clear how leadership competencies interact with these individual variables to subsequently influence employee performance. In response to the leadership competency gap and poor performance in the municipalities, the present study sought to address this by developing a leadership competency and employee performance model. In pursuit of this aim, specific objectives were set at the onset: to develop a conceptual leadership competency and employee performance model for municipalities in South Africa, to theoretically explain the relationships between variables in the proposed leadership competency and employee performance model using previous literature, and to determine the predictive validity of the proposed leadership competency and employee performance model in municipalities in South Africa. The Explanatory Sequential Mixed Methods design was selected, applying both quantitative and qualitative methods of data collection and analysis. Municipal employees from the top three municipalities in South Africa (City of Johannesburg Metropolitan Municipality, City of Tshwane Metropolitan Municipality and City of Cape Town Metropolitan Municipality) formed the main body of the population for this research study. A simple random sampling method was used, comprising of municipal employees. Technically, the researcher applied a two-stage sampling approach. Firstly, purposive sampling was used to select the top three municipalities. Secondly, simple random sampling was applied to select the participants from the top three municipalities. For the quantitative part of the study, data was collected from 789 participants that included all office-bound employees, as well as junior to middle management (levels 6 and 7). General workers, technical staff (working on roads, potholes, streetlights etc.) and senior management (levels 1 to 5) were not included. With regard to the quantitative component of the study, six standard questionnaires were used: The Leadership Assessment Questionnaire (LAQ) to assess leadership competencies; The Psychological Empowerment Questionnaire (PEQ) to assess employee psychological empowerment; The Spirituality at Work (SAW) questionnaire to measure employee workplace spirituatliy; The Motivation Measure (MM) questionnaire to measure employee motivation; The Organisational Citizenship Behaviour Scale (OCBS) to measure organizational citizenship behaviour and The Employee Performance Scale (EPS) to measure employee performance. The data was analysed emphasising both descriptive statistics and inferential statistics using SPSS and SmartPLS. The analysis emphasised correlations, stepwise multiple regression and structural equation modelling. For the qualitative component of the research, management holding a position not lower than assistant director (levels 1 to 5), were included. The researcher used purposive sampling to select 15 individuals to be interviewed. These leaders were highly skilled in the municipal field and their input was used as confirmation or to add further knowledge or input into the results of the quantitative findings. Semi-structured interviews were conducted, as the researcher aimed at obtaining specific information to gather more insights or explanations from leaders into quantitative findings. Thematic analysis as a qualitative data analysis technique was applied.
Thesis (Ph.D (Business Administration))--University of the Free State, 2022
Keywords: Leadership competencies; high performance leadership competencies; employee empowerment; employee psychological empowerment; employee workplace spirituality; employee motivation; employee citizenship behaviour; employee performance; Metropolitan municipality; local government; bureaucracy; political interference